HISTORICAL TRUTH AND ARTISTIC INTERPRETATION (Scientific journal of the Fergana State University, 2024)
This article talks about the interpretation of issues of historicity and education of the young generation, as well as aspects related to human spirituality in the works of our writers who are effectively creating today's Uzbek prose. Also, the details related to the activity of a historical person or the reflection of past reality is a more complicated process. They can also be interpreted differently in works of art. It is a process related to the writer's level of knowledge, outlook and artistic skills. The creation of works related to the life and fate of any event or historical person in Mozi differs from one another by the writer's approach to life material, artistic-aesthetic mastery, social-philosophical generalizations, and methods of expression. In such a process, the writer's artistic way of thinking and creative individuality are revealed. The most important thing is that the deeper the writer studied the historical reality, the more he was able to connect it with the social, spiritual and moral issues of his time, the more relevant the chosen topic becomes. In this article, this aspect of the issue is mainly explored.